PERBUATAN MELAWAN HUKUM DALAM PERSPEKTIF PASAL 1365 KUHPERDATA DAN HADIS Al-TIRMIDZI NOMOR 1232 - Mujaddid Rais, Fakhri; Arifin, Tajul (Gapenas Publisher, 2023)
Islam teaches various good things and the importance of respecting ownership, be it objects, possessions, etc. In this case, people's freedom to live and socialize if it is not based on good laws and religious teachings, various problems will indeed occur. In this case, the researcher aims to analyze and describe how the regulation regarding the emergence of PMH is reviewed by the Civil Code and also reviewed by Hadith At-Tirmiszi Number 1232. This research uses a descriptive analytical qualitative approach method with library research. This research explains that PMH is regulated in article 1365 of the Civil Code which means behavior that violates other people's rights to the law or any behavior that is contrary to the legal obligations of the perpetrator himself and has consequences in the form of responsibility, namely having to return it to its original state and in Hadith At-Tirmidhi number 1232 Regarding the story of the Prophet's companions, it has an implied meaning that selling goods that are not your own is prohibited and has similarities with the act of violating the law itself. Therefore, awareness of the consequences is the solution to PMH